PERBANDINGAN DAMPAK PENGGUNAAN HEADSET TERHADAP FUNGSI PENDENGARAN PADA PENYIAR RADIO DAN YANG BUKAN PENYIAR RADIO DI KOTA MANADO - Wongso, Lily; Danes, Vennetia R.; Supit, Wenny (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Excessive use of headsets for a long period of time may cause hearing loss. While using a headset, the ears receive sound waves which are converted into electrical pulses transmitted to the auditory cortex via the auditory nerve. Exposures to noises can damage the cochlea hair cells that worsen the degenerative process of the auditory nerve. Radio announcing is one of the professions with a frequent use of a headset. This study aimed to find the difference of the auditory functions between people who used headsets frequently and those who did not use headsets. This was a case-control study consisting of a group of people frequently using headsets (radio announcers, the case group) and a group without using headsets (non-radio announcers, the control group). Each group consisted of 20 respondents aged 20-40 years. Hearing functions were measured by using an audiometer while the noise levels generated by the headsets were measured with a sound level meter. The results showed that by using the Fisher exact test, there was a highly significant relationship between the usage of headsets and the hearing loss of the respondents’ left ears (P = 0.001 <0.01) and right ears (P = 0.010 <0.05). Conclusion: There was a difference of hearing in both ears between the radio announcers and non-radio announcers. Keywords: noise exposure, headset, hearing function, radio announcer. Abstrak: Pemakaian headset berlebih dalam kurun waktu yang lama dapat menimbulkan gangguan pendengaran. Pada penggunaan headset, telinga menerima gelombang suara yang kemudian diubah menjadi pulsa listrik yang diteruskan ke korteks pendengaran melalui saraf pendengaran. Pada telinga yang terpapar bising untuk waktu lama dapat terjadi kerusakan sel-sel rambut di koklea saraf pendengaran yang memperburuk proses degenerasi saraf pendengaran. Penyiar radio merupakan salah satu profesi dengan tingkat pengunaan headset yang cukup tinggi. Penelitian ini bertujuan untuk mendapatkan perbedaan fungsi pendengaran antara pengguna headset dan yang tidak menggunakan headset. Penelitian ini merupakan studi kasus-kontrol (case-control study) dengan melakukan perbandingan antara kelompok yang memakai headset (penyiar radio, kelompok kasus) dan kelompok lainnya yang tidak memakai headset (bukan penyiar radio, kelompok kontrol). Masing-masing kelompok terdiri dari 20 responden berusia 20-40 tahun. Fungsi pendengaran diukur dengan audiometer sedangkan tingkat kebisingan yang ditimbulkan oleh headset di ukur dengan sound level meter. Analisis statistik menggunakan uji Fisher exact menunjukkan terdapat hubungan yang sangat bermakna antara penggunaan headset dan gangguan pendengaran pada telinga kiri (P = 0,001 <0,01) dan telinga kanan (P = 0,010 <0,05). Simpulan: Terdapat perbedaan fungsi pendengaran kedua telinga antara penyiar radio dan yag bukan penyiar radio. Kata kunci: paparan bising, headset, fungsi pendengaran, penyiar radio.